Web components: a comparison between web services and software components - Iribarne, Luis (Revista Colombiana de Computación, 2004)
The software engineering discipline is experiencing a quick consolidation in the applications development activities and the use of technologies and methodologies of web-based programming. In the web services arena some oriented and based practices for the construction of large scale software applications (i.e., distributed information systems) are beginning to appear. Keywords: Web services, software components, WSDL, UDDI, semantic specification, protocol specification.